Quasispecies of TT Virus (TTV) with Sequence Divergence in Hypervariable Regions of the Capsid Protein in Chronic TTV Infection - Nishizawa, Tsutomu (American Society for Microbiology, 1999)
Three hypervariable regions were identified in a central portion of open reading frame 1 of TT virus DNA, which codes for a putative capsid protein of 770 amino acids. TT virus circulates as quasispecies, with many amino acid substitutions in hypervariable regions, to evade immune surveillance of the hosts and to establish a persistent infection.